Initial teacher education curricula, basic professional identities and professional trajectory | Currículos de formación inicial identidades profesionales de base y trayectoria profesional - Amélia Lopes (2007)
With the objective of studying the role of initial teacher education in the construction of primary teachers' identities, this paper characterizes and relates the teacher education curricula concerning 4 periods of the last 30 years (through documental analysis) with the basic professional identities, the professional trajectories and the current identities of teachers formed in those periods (through biographical analysis). The conclusions indicate that each particular curriculum produces different basic professional identities (from 1974 on with a quality which is, at least, average), but also that, in the professional trajectory, these identities end up by being similar and, generally, less rich. It is emphasized the need to invest, in elementary school, in the quality (exigency) of the working contexts.